Perlindungan Hukum Hak Cipta Lagu dalam Konteks Layanan Streaming Digital - Yumna Shafa Azzahra; Dudung Hidayat; Raden Handiriono (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the legal protection and certainty of songwriters' economic rights against the misuse of personal digital streaming services in public spaces for commercial purposes. This study uses a normative juridical method. The results show that Law Number 28 of 2014 and Government Regulation Number 56 of 2021 normatively require licensing and royalty payments for commercial use. However, their implementation remains hampered by low business compliance, weak law enforcement, minimal transparency in royalty distribution, and platform dominance that weakens creators' control. Therefore, regulatory strengthening, technology-based transparency, and more equitable royalty distribution reform are urgently needed.